Dainavà. Vardo reikšmė, istorija ir kilmė - Karaliūnas, Simas (Baltistica, 2006)
Dainavà. MEANING, HISTORY AND ORIGIN OF THE NAMESeveral villages in Southern Lithuania bear the name Dainavà (acc. sg. Daĩnavą). There is a village of this name, inhabitated by the Lithuanians, also in Byelorussia, in Grodno region, Zietela district (in Byelorussian Dziatlovo as well as Diatlovo). The name is attested in 13th c. historical sources written in Latin: Deynowe, Denowe. In 16th c. Russian chronicles we find Doinova (Дойнова). It has been long ago assumed by investigators that this was the Lithuanian name for the Yatvingians, a tribe of the Western Balts. In addition to this, there are ten villages in Aukštaičiai (in the Highlands of Lithuania) called Dainiaĩ. It was suggested by historians that in some cases these villages got the name from the name plur. *dainiaĩ (sg. *dainỹs) of the population of the Dainava region.In Lithuanian there are adjectives dienì and dienė̃ „pregnant, with calf, in foal” (
Keywords: Dainava; etimologija